Fenología y constante térmica de la pitahaya roja (Hylocereus undatus Haw) - Murillo Paz, Ángel Steveen (2023)
The main objective of this research work was to evaluate the phenology and thermal constant of red pitahaya (Hylocereus undatus Haw), in Bolívar canton, Manabí province. This is a non-experimental research, that is, the variables were not manipulated, it is based fundamentally on the observation of the different phenological changes of the red pitahaya and how they are affected by the accumulation of heat. The six phenological stages of red pitahaya were studied: development of the vegetative bud, development of vegetative propagation organs, reproductive development, flowering, fruit development and fruit ripening according to the BBCH scale extended for one year, for which 20 posts were selected for evaluation, where constant monitoring of the phases was carried out. Meteorological data were recorded for each phenological stage. The results obtained determined that the red pitahaya needed 90 days to complete its cycle in the rainy season, from the appearance of vegetative buds to the overripening of the fruits; on the contrary, in the dry season these same phases took 89 days, with an average maximum temperature of 30.10°C with a minimum of 18.4°C.